2011
DOI: 10.1002/zaac.201100094
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Molecular Structure of Bis(ethylenediamine)acetatonickel(II)hexafluoridophosphate Complex [Ni(en)2(CH3CO2)]PF6. An Unexpected Acetylacetonato Cleavage Reaction

Abstract: The title complex was synthesized by an unusual reaction between [Ni(acac) 2 (H 2 O) 2 ] and ethylenediamine in water solution. The crystal structure of 1 shows the nickel(II) core in a tetragonally distorted octahedral environment coordinated to two ethylenediamine molecules and one acetate ligand. This is the first example of a mononuclear bis(ethylenediamine)nickel(II) complex, where the oxygen at-* Dr. F. S. Nunes E-Mail: fsnunes@ufpr.br [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…For 8, there are two molecules of CH 2 Cl 2 per formula unit. CCDC-827741 (5·C 4 H 10 O), CCDC-827742 (6), and CCDC-827743 (8·2 CH 2 Cl 2 ) contain the supplementary crystallographic data for this paper. These data can be obtained free of charge from The Cambridge Crystallographic Data Centre via www.ccdc.cam.ac.uk/data_request/cif.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For 8, there are two molecules of CH 2 Cl 2 per formula unit. CCDC-827741 (5·C 4 H 10 O), CCDC-827742 (6), and CCDC-827743 (8·2 CH 2 Cl 2 ) contain the supplementary crystallographic data for this paper. These data can be obtained free of charge from The Cambridge Crystallographic Data Centre via www.ccdc.cam.ac.uk/data_request/cif.…”
Section: Methodsmentioning
confidence: 99%
“…The products of each aerobic photochemical reaction were determined after irradiating a 0.002 m solution of each complex (4)(5)(6) in acetonitrile at 350 nm for 20 h, under an aerobic atmosphere. The Ni II -containing products were identified by using 1 H NMR spectroscopy ( Figures 5-7) and ESI-MS.…”
Section: Complex Synthesis and Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…As it was mentioned earlier the oxidative reactivity of unsubstituted diketonate substrates by Nickel(II) complexes has been reported. 21,22,35 The conclusions from this work showed that unsubstituted diketonates e.g. acetylacetonate, are generally unreactive towards oxidative cleavage.…”
Section: Proposed Mechanism For Reactivitymentioning
confidence: 80%